2020
DOI: 10.1186/s40794-020-00119-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, antimicrobial susceptibility pattern, and associated factors of Salmonella and Shigella among food handlers in Adigrat University student’s cafeteria, northern Ethiopia, 2018

Abstract: Background Food handlers play a significant role in the transmission of foodborne infections. Salmonella and Shigella are the most common foodborne pathogens and their infections are a major public health problem globally. Thus, this study aimed to determine the prevalence, antimicrobial susceptibility patterns, and associated factors of Salmonella and Shigella colonization among food handlers. Methodology A cross-sectional study was conducted from March to August 2018 at Adigrat University student cafeteria… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…In this study, the magnitudes of Salmonella species among food handlers were 16 (5.5%). This was comparable to studies carried out in Northern Ethiopia, Adigrat (7.3%) ( 39 ), Southern, Ethiopia, Arba Minch (6.9%) ( 42 ), and Nigeria, (5.5%) ( 49 ). However, our result was higher than the studies reported from Ethiopia, Addis Ababa (3.5%) ( 46 ), Bahir Dar (1.6%) ( 23 ), and Gondar (3.1%) ( 50 ).…”
Section: Discussionsupporting
confidence: 84%
“…In this study, the magnitudes of Salmonella species among food handlers were 16 (5.5%). This was comparable to studies carried out in Northern Ethiopia, Adigrat (7.3%) ( 39 ), Southern, Ethiopia, Arba Minch (6.9%) ( 42 ), and Nigeria, (5.5%) ( 49 ). However, our result was higher than the studies reported from Ethiopia, Addis Ababa (3.5%) ( 46 ), Bahir Dar (1.6%) ( 23 ), and Gondar (3.1%) ( 50 ).…”
Section: Discussionsupporting
confidence: 84%
“…However, the prevalence of NTS in caretakers (7.5%), in the present study is comparable to the earlier report of study conducted on asymptomatic food handlers in Ethiopia. 77,78 Attributing to our study, Getie et al 30 also reported GNEBPs like Shigella spp., enterohemorrhagic, E. coli (EHEC), and S. enterica as important pathogens among asymptomatic food handlers. The higher prevalence of enteric bacterial FBPs in caretakers might also due to the small sample size considered in this particular study.…”
Section: Discussionsupporting
confidence: 80%
“…However, the prevalence of NTS in caretakers (7.5%), in the present study is comparable to the earlier report of study conducted on asymptomatic food handlers in Ethiopia. 77 , 78 …”
Section: Discussionmentioning
confidence: 99%
“…This was comparable with previous reports in India 0.53% [46] and in Fijji 0.7% [47]. Besides, this study is lower than a study conducted in Ethiopia: Addis Ababa (4.1%) [48], in Ethiopia: Adigrat (7.3%) [49], Yemen 20% [50], in Nepal (3.1%) [51], and in Bangladesh (5%) [52]. The discrepancies in all of the above comparisons could be attributed to the fact that different, countries and within countries may be due to applying different test methods for the isolation of Salmonella species, economic status, characteristics of study participants, and epidemiological distributions of the pathogenic bacteria.…”
Section: Plos Onesupporting
confidence: 87%